Resistance to Antisocial Peers in Adolescents Found Not Criminally Responsible on Account of Mental Disorder: Predictive and Incremental Validity With the VRAG-R - Patricny, Nicol (Criminal justice and behavior, 2022)
There has been a recent theoretical shift toward the inclusion of protective factors within risk assessment. However, there is a lack of empirical evidence surrounding this practice in unique forensic populations. Using a long-term retrospective design, we examined the predictive and incremental validity of the protective factor resistance to antisocial peers and the Violence Risk Appraisal Guide—Revised in 119 individuals who were found Not Criminally Responsible on Account of Mental Disorder (NCRMD) as adolescents. The results indicated that resistance to antisocial peers significantly predicted general nonrecidivism (area under the curve [AUC] = .647) and violent nonrecidivism (AUC = .654) in the long term (maximum 35-year follow-up). Incorporation of resistance to antisocial peers into the Violence Risk Appraisal Guide—Revised did not significantly increase the incremental validity for general or violent recidivism. Using logistic regression, adolescents’ age at their NCRMD start date had no significant relationship with recidivism and was unrelated to the protective effect of resistance to antisocial peers.